Hydrotherapy in the treatment of cardiorespiratory sequelae in the post-covid (Research, Society and Development, 2022)
Objective: To verify the effects that hydrotherapy develops in individuals who were contaminated by COVID-19 and who presented cardiorespiratory sequelae in their chronic phase. Methodology: It is quantitative, approved by the Research Ethics Committee (CEP) of the State University of Pará (UEPA), campus XII, CAAE 54993622.2.0000.5168, in which it followed the rules of the National Council for Health and Research with Human Beings, resolution 510/2016. Its target audience was individuals who contracted COVID-19, manifesting in its acute phase mild to severe cases of the disease, and developed long-term cardiorespiratory sequelae. Results: Research carried out with thirteen participants in which the largest number of participants were female (53.85%) with an average age of 42.2 years, followed by males (46.15%) with an average age of 49.8 years old; Of the symptoms reported during the chronic phase, it is possible to observe fatigue as the main persistent symptom (92.31%), followed by dyspnea (46.15%) and myalgia (23.08%). Conclusion: It is known that COVID-19 leaves sequelae both in patients who became infected and had mild and severe symptoms, such sequelae require early rehabilitation, as the patient's chances of full recovery are greater; observed and obtained positive results regarding the influence of hydrotherapy in improving the hemodynamic stability and physical conditioning of the patient, contributing scientifically to the practice of rehabilitation.